Carboxymethylcellulose from Bleached Organosolv Fibers of Eucalyptus Nitens: Synthesis and Physicochemical Characterization - Moya-Duran, S; Moya-Duran, S; Matsuhiro-Yamamoto, B; Matsuhiro-Yamamoto, B; Romero-Figueroa, J; Yanez-Sanchez, M; Serafini, D (Springer Netherlands, 2018)
The objective of the present study was to synthesize sodium carboxymethylcellulose from Eucalyptus nitens cellulose. The cellulose extraction was carried out in three stages. In the first stage, E. nitens wood was fractionated using an organosolv pretreatment (methanol–water 50% v/v, 45 min at 200 °C) followed by an alkaline extraction (NaOH, 1.5 M). Finally, the organosolv pulp was bleached using NaClO2 (1.3% w/v, pH 3.8). The bleached cellulose obtained was converted to sodium carboxymethylcellulose (NaCMC) by an etherification reaction in isopropanol medium. NaCMC structure, morphology and properties were researched using FTIR, 1H and 13C NMR spectroscopy, scanning electron microscopy, and thermogravimetric analysis. The results indicate substitution mostly occurred mostly at the C-6 position of 1 → 4 β-d-glucopyranosyl residues of cellulose chains. © 2018, Springer Science+Business Media B.V., part of Springer Nature.